Positive Discipline as a Transformative Approach to Strengthening Students’ Worship Practices - Elza Eka Putri; Hendra Harmi; Dewi Purnama Sari (Newinera Publisher, 2025)
The formation of worship practices in Islamic boarding schools cannot be reduced to rule enforcement or ritual scheduling, because students’ engagement in worship grows through relationships, emotional experiences, and the meaning they construct in daily life. This study argues that positive discipline becomes transformative only when it is lived as a humane, relational, and spiritually grounded practice within the pesantren environment. Through a phenomenological exploration of teachers, caregivers, and students at Madinatul Ulum Pamenang, the research reveals that the shift from punitive control to a compassionate and dialogic approach fundamentally reshapes how students understand and perform worship. Rather than compelling compliance, teachers cultivate commitment by modeling sincerity, guiding students through reflective conversations, and creating rhythms of life where worship becomes integrated into personal identity. Students internalize worship not because they fear reprimand but because they witness authentic devotion, receive empathetic support, and participate in structured routines that gradually evolve into personal habits. The findings show that positive discipline functions less as a technique and more as a moral culture that nurtures students’ responsibility, emotional maturity, and spiritual awareness. In this environment, worship becomes an expression of inner readiness instead of external obligation. This study demonstrates that when discipline is reframed as a relational and meaning-oriented process, pesantren life provides fertile ground for cultivating enduring spiritual practices that students sustain even beyond institutional supervision.